2016
DOI: 10.1016/j.aquaculture.2016.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of microbiota in larval culture of Pacific oyster, Crassostrea gigas

Abstract: This study has two main objectives: (1) to implement a recycling aquaculture system (RS) for the larvae of the oyster Crassostrea gigas, and (2) to characterise the bacterial communities established in different compartments of this system. An RS with 25% fresh seawater addition per hour and another with no addition (0%) were compared with a flow-through system (FT). Larval survival was equivalent in RS and FT, but growth rate was 17% slower in RS than in FT. The physical chemical parameters remained stable, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 43 publications
3
28
0
1
Order By: Relevance
“…Both systems correctly functioned until 150 larvae mL À1 . A previous experiment using the same FTS with Crassostrea gigas larvae at 50 and 100 larvae mL À1 showed similar results (da Costa et al, 2015), while a comparison between FTS and RAS at 50 larvae mL À1 (Asmani et al, 2016) revealed a growth deficit in RAS. Equivalent performances were previously obtained with an FTS in a 150-L tank (Rico-Villa et al, 2008, 2009.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Both systems correctly functioned until 150 larvae mL À1 . A previous experiment using the same FTS with Crassostrea gigas larvae at 50 and 100 larvae mL À1 showed similar results (da Costa et al, 2015), while a comparison between FTS and RAS at 50 larvae mL À1 (Asmani et al, 2016) revealed a growth deficit in RAS. Equivalent performances were previously obtained with an FTS in a 150-L tank (Rico-Villa et al, 2008, 2009.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, a few opportunists such as V. aestuarianus and Vibrio neptunius were present at very low levels in both systems. The filamentous bacteria found in this study have not yet been reported in the formation of biofilm in aquaculture systems, particularly in bioreactors (Schneider et al, 2007;Blancheton et al, 2013;Ruan et al, 2015;Asmani et al, 2016). These were however encountered when OM was abundant, as in sludge, wastewater, and sediment (Lu et al, 2013;Gonzalez-Gil et al, 2015;Raulf et al, 2015).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations